Matthiola shiraziana (Brassicaceae), a new species from Dena region, Iran - Zeraatkar, Amin; Ghahremaninejad, Farrokh; Al-Shehbaz, Ihsan A.; Khosravi, Ahmad R.; Assadi, Mostafa (Phytotaxa, 2016)
Matthiola shiraziana, a new species from Iran, is described and illustrated. It is compared with the closely related M. flavida Boiss. and M. ovatifolia (Boiss.) Boiss. A full description and detailed stereomicroscopic micrographs and diagnostic morphological features are provided on the basis of the specimens housed in several Iranian herbaria.